Evaluation of the longitudinal strength of a body frame in consideration of plastic regions using non-linear dynamic analysis - Toyokazu HAMAJIMA; Kazuhiko NISHIMURA; Yoshiaki TERUMICHI (Nihon Kikai Gakkai ronbunshu, 2014)
In recent years, much dynamic analysis and structural analysis have been done while considering abnormalities, such as derailment and collisions with foreign objects. In such situations, longitudinal force that exceeds design load may be applied to the car body and the ultimate load, also known as the buckling load and the crippling load, are more important than the design load that stipulates elastic strength. This is because a buckling load is the maximum load that a structure can sustain its soundness in the event of an accident. In this paper, the longitudinal strength of a railway vehicle is evaluated in consideration of plastic deformation. First in order to evaluate the strength of the railway vehicle body experimentally and validate the finite element (FE) model for the numerical simulations, the full scale crash test is conducted. Next the numerical simulations were conducted to investigate the relationship between the ultimate load and the design load, and effects on the buckling locations caused by load conditions such as dynamics and load path. As a result, it is clarified that existing vehicle structures have much larger longitudinal ultimate strength than elastic strength as defined in standards. Finally the ratios of the ultimate load to the design load are clarified, quantitatively.